Advances on Cyclocarya paliurus polyphenols: Extraction, structures, bioactivities and future perspectives. (1st December 2022) - Zhao, Jinjin; Wang, Zhangtie; Xu, Deping; Sun, Xiulan
Highlights: C. paliurus leaves are traditional medicinal plants and food raw materials. A large number of polyphenols are identified in C. paliurus . C. paliurus polyphenols possess many excellent bioactivities. Potential mechanisms of C. paliurus polyphenols are discussed. Abstract: Cyclocarya paliurus ( C. paliurus ) is an edible and medicinal plant, distributed in southern China. As a kind of new food raw material, the leaves of C. paliurus are processed as tea products in daily life. C. paliurus is recognized as a good source to polyphenols, showing excellent bioactivities, which has attracted more and more attention. Polyphenols are important functional bioactive components in C. paliurus . C. paliurus polyphenols perform nutritional functions in anti-diabetes, anti-hyperlipidemic, anti-obesity, anti-oxidant, and other activities. In this review, we summarize the research progress of extraction technologies, structural characteristics, and bioactivities of C. paliurus polyphenols. Other potential functions of C. paliurus polyphenols are prospected. This review provides a reference for further research and applications of C. paliurus polyphenols in a field of functional food and medicines.